Implementasi Pendekatan Values Clarification Technique (VCT) Berbantu Pop Up Book dalam Pembelajaran IPS di SD - Habibi, Muhamad Ridwan; Yuliani, Meri; Gazali, Munawir; Zaitiun, Zaitiun (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Education has a goal, namely to give birth to a generation that is intelligent, high quality, characterized and cultured. One of the goals of this education is to give birth to a generation of character, meaning that it is very important for students to instill good character. Teachers must familiarize students with instilling good values in students so that they will not only understand the material but instill good values that are important to apply. By using the VCT Approach with the help of Pop Up Books as a learning medium to increase students' curiosity in learning social studies, where social studies studies social sciences, there are values contained in each material. The aim of this research is to examine the application of the VCT approach assisted by Pop Up Books in class IV social studies learning at SDN Sumbek. The method used uses descriptive qualitative methods, with data collection through observation, interviews and documentation. Based on the data obtained, the application of the VCT approach assisted by Pop Up Books has been implemented well which can increase students' awareness in instilling the values that will be applied. It is hoped that this research will be useful to related parties who can benefit from it, such as school principals, teachers and students, as well as future researchers.